PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 016 SEKELADI KECAMATAN TANAH PUTIH - Suriani '; Hendri Marhadi; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is a classroom action research (CAR) conducted aims to improve learning outcomes IPA fourth grade students of SDN 016 Sekeladi by applying inquiry learning model. Formulation of the problem: Does the implementation of inquiry learning model can improve learning outcomes IPA grade IV SDN 016 Sekeladi Tanah Putih Hilir.Penelitian Rokan was held on 13 April 2016 until May 4, 2016 with 2 cycles. The subjects were students of class IV SDN 016 Sekeladi totaling 18 people who used the data source. Data collection instrument in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results obtained from the study before action replay value with an average of 62.22, an increase in the first cycle with the average being 72.05. In the second cycle increased by an average of 80.56. Activities teachers in the learning process in the first cycle, the first meeting of 58.33%, and a second meeting be 66.66%. At the first meeting of the second cycle of 75%, and the second meeting increased to 83.33%. The results of the data analysis activities of students in the first cycle of the first meeting and the second meeting of 54,13% increase to 62.50%. In the second cycle to the first meeting of 70.83%, and the second meeting increased to 83.33%. The results of the study in class IV SDN 016 Sekeladi prove that the implementation of inquiry learning model can improve learning outcomes IPA grade IV SDN 016 Sekeladi Tanah Putih. Key Words: Learning Model Inkuri, Learning Outcomes IPA